The Teaching Model of Arabic Language Teachers in Improving the Arabic Language Skills of Students at Muhammadiyah Kwala Madu Langkat Pesantren - Rambe, Nadiatul Ulyah; Ruslan, Muhammad (Electronic Journal of Education, Social Economics and Technology, 2025)
Arabic is a subject taught at the Muhammadiyah Kwala Madu Langkat Islamic Boarding School. The teaching model of a teacher greatly influences the Arabic language proficiency of the students at the Islamic boarding school. Therefore, Arabic language teachers must have specific models and strategies in developing the Arabic language skills of the students. This research aims to identify the teaching models used by teachers to improve Arabic language skills, the obstacles faced by teachers in enhancing Arabic language proficiency, and how to overcome these obstacles at the Muhammadiyah Klawa Madu Langkat Islamic boarding school. The research method used in this study is qualitative research. The results of this study indicate that an effective teaching model involves the use of interactive methods and engaging learning media. It is hoped that teachers can create a pleasant learning environment, so that students are more motivated to actively participate in learning. Overall, this research emphasizes the importance of the teacher's role in designing and implementing appropriate teaching models to enhance Arabic language skills among students.Based on the research conducted, it is uniquely found in this study a model in Arabic language teaching that uses an immigrant model, which runs in parallel between the students' linguistic understanding and their use of the Arabic language. This teaching model is considered very effective in improving the students' skills in using the Arabic language.